Pengabdian Menumbuhkan Minat Baca Melalui Pojok Baca Pada Siswa SDN Waruberon, Sidoarjo - Lely Agustin; Endang Indartuti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
There is a deficiency in facilities and infrastructure, notably the absence of library space for reading activities. The books at SD Negeri Waruberon are not very engaging, and the reading material is overly challenging. This discourages students from dedicating time to reading books. They tend to engage in less productive activities with their friends, as they find these activities more interesting and enjoyable. In addition to the absence of supporting infrastructure, there are also environmental and familial factors. Many parents choose to provide their children with cellphones or gadgets rather than purchasing engaging books that cater to their needs. This significantly diminishes the interest in reading at SD Negeri Waruberon. For this reason, the service conducted by college students placed at SD Negeri Waruberon is intended to boost the reading interest of SD Negeri Waruberon students through the Reading Corner program. Having a reading corner in each of their classrooms means they have a comfortable space to read books and utilize their free time for meaningful activities that expand their knowledge. Additionally, various methods are employed, including: 1) Planning / Making a design, 2) Demonstrating Design Outcomes, 3) Gathering and Analyzing Information, 4) Implementing the Manufacturing Process. A program to establish a reading corner at SD Negeri Waruberon in Sidoarjo has delivered positive results. The students at SD Negeri Waruberon have shown an increased interest in reading books during their free time. They have developed a deeper understanding of the importance of reading, which has enhanced their insight and critical thinking abilities. Moreover, they have become more confident in expressing their opinions, both individually and with their peers. They find it easier to comprehend conveyed information, and their intellectual capabilities have improved. Additionally, their level of literacy activities has increased, enabling them to create stories, rhymes, and poems, which are periodically displayed on the school wall.